To Naturalize is to Differentiate - Ruper, Stefani (Method & theory in the study of religion, 2018)
Many scholars have expressed fears that naturalism will homogenize religion, thereby reifying the concept and distorting the academy’s perception of local cultures. Yet this fear is misplaced. In fact, recent advances in cognitive science, most notably regarding the development of interactional theories of cognition, lend significant support to conceptualizing religion heterogeneously. In this paper I first explore Russell McCutcheon’s rationale for fearing naturalism. I then obviate McCutcheon’s fears by demonstrating how the interactionalist perspective in cognitive science both promotes a heterogeneous understanding of human behavior as well as refutes sui generis religion. I conclude by recommending fusing insights from interactionalism with a ground-up, sociological approach to “religion” such as Timothy Fitzgerald’s, which results in research methodology that is appropriately sensitive to the natural differences of behavior that have been historically identified as religious.